2017
DOI: 10.1007/s00120-017-0338-z
|View full text |Cite
|
Sign up to set email alerts
|

Nebenwirkungen der Chemotherapie

Abstract: Urologic tumors are frequently treated by multimodal therapeutic strategies with the consequence of an increasing number of adverse events. The most common chemotherapy-induced side effects are neutropenia, stomatitis, mucositis, diarrhea, and emesis. The efficacy of tumor therapy can be improved by good prophylaxis and standardized management of side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…Cancer is typically treated by conventional therapies such as chemotherapy, radiotherapy, and surgery. Although all these therapies seem to be very effective for killing cancer cells in theory, in fact, these nonselective therapies also introduce a lot of serious side effects [113,114]. Recently, nanotechnology-based nanosystems, with high biocompatibility, easily surface functionalization, cancer targeting, and drug delivery capacity, have demonstrated the potential to overcome these side effects.…”
Section: In Vitro and In Vivo Anticancerous Activity Of Zno Npsmentioning
confidence: 99%
“…Cancer is typically treated by conventional therapies such as chemotherapy, radiotherapy, and surgery. Although all these therapies seem to be very effective for killing cancer cells in theory, in fact, these nonselective therapies also introduce a lot of serious side effects [113,114]. Recently, nanotechnology-based nanosystems, with high biocompatibility, easily surface functionalization, cancer targeting, and drug delivery capacity, have demonstrated the potential to overcome these side effects.…”
Section: In Vitro and In Vivo Anticancerous Activity Of Zno Npsmentioning
confidence: 99%
“…Several studies have reported correlation between genotype B and symptomatic acute giardiasis, but both genotypes A and B are capable of producing symptoms (Einarsson et al, 2016;Pijnacker et al, 2016;Puebla et al, 2017). In this investigation, all patients that participated in this study were undergoing chemotherapy, which usually leads to intestinal disorders (Hauner et al, 2017), a fact that makes correlation between symptoms and G. lamblia more difficult.…”
Section: Discussionmentioning
confidence: 94%
“…Can kill hidden cancer cells. But chemotherapy is often used after other treatments, because there are still some raw cancer cells left after surgery kills them [8]. Consider scheduling other treatments, such as neoadjuvant therapy.…”
Section: Another Special Treatment For Hpv Virus-chemotherapymentioning
confidence: 99%